PENGARUH JARAK TANAM DALAM TUMPANGSARI SORGUM MANIS (Sorghum bicolor L. Moench) DAN DUA HABITUS WIJEN (Sesamum indicum L.) TERHADAP PERTUMBUHAN DAN HASIL - , RIANNI CAPRIYATI ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Sweet sorghum is a C4 plant that planted in spacing of 70 cm Ã 25 cm or 75 cm Ã 20 cm. Spacing of sweet sorghum still wide enough to optimize land productivity by applying intercropping. Sweet sorghum can be intercropped with sesame, which is C3 plant. The research was conducted to determine interaction between spacing of sweet sorghum and sesame habitus, to obtain optimal spacing of sweet sorghum and appropriate sesame habitus when intercropped with sweet sorghum. The field experiment was conducted from May to August 2013 in Tridharma farm, Banguntapan, Bantul. Design of the experiment used Randomized Complete Block Design with two factors. The first factor consists of three spacing of sweet sorghum (60 cm Ã 25 cm, 70 cm Ã 25 cm, and 80 cm Ã 25 cm). The second factor consists of two sesame habitus of branching (Winas-1) and unbranched (Sumberejo-2). The data were analyzed with analysis of variance Î±= 5 %, continued by Duncanâs Multiple Range Test Î±= 5 %. The result of this research showed that there was interaction between spacing treatment of sweet sorghum with two sesame habitus of the number of leaves of sweet sorghum at 8 week after planting and light interception on the leaves at 8 week after planting. Spacing sweet sorghum of 70 cm Ã 25 cm were giving LER at 1,73 that as good as spacing of 80 cm Ã 25 cm. Sesame Winas-1 with branching habitus could grow well and produce higher LER (1,71) than sesame SBR-2 (1,41) when intercropped with sweet sorghum.